The relationships between upper extremity muscle strength and endurance with respiratory function, functional capacity and quality of life in children and adolescents with cystic fibrosis - Maden, Çağtay; Bayramlar, Kezban; Maden, Tuba; Sağlam, Melda; Eltan, Sevgi Bilgiç; Keskin, Özlem (MA Healthcare Ltd)
Background/aims The number of studies exploring isolated upper extremity muscle strength and endurance in paediatric patients with cystic fibrosis is limited. The aim of this study was to investigate the relationship between upper extremity muscle strength and endurance with respiratory functions, functional capacity and quality of life in children and adolescents with cystic fibrosis. Methods Children and adolescents with cystic fibrosis performed a flexed arm hang test to measure muscle endurance, movement against a dynamometer to measure muscle strength, a pulmonary function test and 6-minute walk test to measure functional capacity. The Cystic Fibrosis Questionnaire Revised was used to assess quality of life. Results A total of 29 children and adolescents with cystic fibrosis (15 girls, 14 boys) participated in the study. Biceps muscle strength moderately correlated with forced expiratory volume in 1 second predicted percentage, forced vital capacity predicted percentage and the ratio of forced expiratory volume in 1 second to forced vital capacity predicted percentage (r=0.306, P=0.035; r=0.405; P=0.029; r=0.367, P=0.048, respectively). Biceps muscle strength, shoulder abductors muscle strength, hand grip strength and flexed arm hang test correlated with the ratio of forced expiratory volume in 1 second to forced vital capacity predicted percentage. Biceps muscle strength, shoulder abductors muscle strength, hand grip strength and flexed arm hang test correlated with 6-minute walk test distance (r=0.678, p<0.001; r=0.732, p[removed]
Keywords: 6-minute walk test; Cystic fibrosis; Muscle strength; Pulmonary function; Quality of life